Hard alloy holding-up hammer for synthesizing high-purity large monocrystal diamond and preparation method of hard alloy holding-up hammer
By employing a multi-component cemented carbide top hammer composed of WC, Co, TaC, TiC, and Cr3C2 and a gradient sintering process, the failure problem of traditional top hammers under ultra-high pressure and high temperature was solved, achieving efficient and stable synthesis of high-purity large single-crystal diamond and improving the durability and purity of the material.
Patent Information
- Application Number
- CN202511289568.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-10
- Publication Date
- 2025-12-30
AI Technical Summary
Traditional cemented carbide top hammers are prone to cracking and failure under ultra-high pressure above 6GPa and high temperature of 1300-1600℃, resulting in poor material stability and reduced purity of synthesized diamond. Existing preparation processes cannot achieve both density and uniformity, affecting the synthesis efficiency and quality of high-purity large single crystal diamonds.
A cemented carbide top hammer is prepared using a multi-component cemented carbide material composed of WC, Co, TaC, TiC, and Cr3C2 through a gradient sintering process, including ball milling, cold pressing, cold isostatic pressing, and gradient sintering, combined with cryogenic treatment to improve the high-temperature stability and density of the material.
Under conditions of 6GPa/1500℃, the hardness and compressive strength are significantly improved, the service life is increased to more than 100 cycles, there is no cracking, the diamond purity is increased to 99.99%, and the batch stability of the material is better than that of existing technologies.
Abstract
Description
Technical Field
[0001] This invention belongs to the field of cemented carbide technology for the synthesis of superhard materials, specifically relating to an ultra-high pressure, high temperature stable composite cemented carbide top hammer suitable for the synthesis of high-purity large single crystal diamond and its preparation process, especially suitable for synthesis scenarios under ultra-high pressure above 6GPa and high temperature environment of 1300-1600℃. Background Technology
[0002] In the synthesis of high-purity large single-crystal diamond, the cemented carbide top hammer, as a core component, must withstand extreme environments of ultra-high pressure and high temperature for extended periods. Its performance directly determines the synthesis efficiency, diamond quality, and production cost. Currently, existing technologies face the following key challenges:
[0003] 1. Insufficient resistance to extreme environments: Traditional cemented carbide top hammers (such as single WC-Co systems) are prone to cracking and failure under ultra-high pressure above 6GPa and high temperature of 1300-1600℃ due to grain boundary slip, phase transformation or thermal stress concentration, resulting in short service life (usually only a few dozen synthesis cycles) and seriously affecting the continuity of production.
[0004] 2. Poor material stability: Some top hammer materials are prone to component diffusion or structural changes under high temperature and pressure due to unreasonable composition design, which leads to impurity contamination of the synthesized diamond and a decrease in purity (such as excessive oxygen content and metal impurities), making it difficult to meet the quality requirements of high-purity large single crystals.
[0005] 3. Defects in the preparation process: Existing sintering processes (such as conventional hot pressing and isostatic pressing) cannot simultaneously ensure the density and uniformity of the material. Residual pores or uneven grain distribution will exacerbate local stress concentration, further reducing the compressive strength and wear resistance of the top hammer.
[0006] Although existing technologies have been improved by adding a single carbide (such as TiC or TaC) or optimizing sintering parameters, they still cannot simultaneously solve the synergistic problems of ultra-high pressure and high temperature stability, compositional purity and microstructure uniformity, which restricts the efficient synthesis of high-purity large single crystal diamond. Summary of the Invention
[0007] This invention provides a cemented carbide top hammer and its preparation method for the synthesis of high-purity large single-crystal diamond, which effectively solves the failure problem of traditional top hammers, meets the requirements for efficient and stable synthesis of high-purity large single-crystal diamond, and has significant industrial application value.
[0008] The present invention solves the above-mentioned technical problems through the following technical solution:
[0009] A cemented carbide top hammer for synthesizing high-purity large single-crystal diamond, the top hammer being composed of the following components by weight percentage:
[0010] WC: 80%–88%;
[0011] Co: 4%–8%;
[0012] TaC: 2%–5%;
[0013] TiC: 3%–7%;
[0014] Cr3C2: 0.5%–2%;
[0015] Among them, WC is the hard phase, Co is the binder phase, TaC inhibits grain growth and enhances high-temperature stability, TiC forms a pinning effect through the dispersed distribution of nanoparticles, and Cr3C2 is used to improve the wettability of the Co phase and enhance its oxidation resistance.
[0016] In one specific embodiment, the WC powder has a purity of ≥99.9% and a particle size of 0.4–0.8 μm; the Co powder is a spherical powder with a purity of ≥99.5% and a particle size of 0.8–1.2 μm.
[0017] In a specific embodiment, the TaC powder is a nanoparticle with a particle size of 50-100 nm; the TiC powder is a nanoparticle with a particle size of 10-30 nm; and the Cr3C2 powder is a powder with a particle size of 10-30 μm.
[0018] A method for preparing a high-pressure resistant cemented carbide hammer material includes the following steps:
[0019] (1) Raw material mixing: WC, Co, TaC, TiC and Cr3C2 are mixed according to weight percentage and ball-milled for 36 to 60 hours under argon protection using a planetary ball mill;
[0020] (2) Drying and sieving: The mixed powder is vacuum dried at 80-100℃ for 4-6 hours and then sieved through a 200-mesh sieve under argon protection;
[0021] (3) Cold pressing and cold isostatic pressing: The powder is cold pressed into shape at 20-100MPa and then subjected to cold isostatic pressing at 200-400MPa;
[0022] (4) Gradient sintering: In a vacuum sintering furnace, degassing preheating (800℃, 1h), liquid phase sintering (1350~1450℃, 10~20MPa, 2~3h) and slow cooling treatment (3℃ / min to 800℃, then naturally cooled to room temperature) are carried out in sequence.
[0023] (5) Post-treatment: The sintered top hammer is ground to make the surface roughness ≤0.8μm; and liquid nitrogen cryogenic treatment is performed, the temperature is lowered to -150℃, held for 4h, and then heated to room temperature.
[0024] In one specific embodiment, the ball-to-material ratio during ball milling is 7.5:1, and anhydrous ethanol is used as the ball milling medium.
[0025] In one specific embodiment, the holding time for cold isostatic pressing is 20 to 40 minutes, and the depressurization rate is 50 MPa / minute.
[0026] In a specific embodiment, the preferred conditions for the liquid phase sintering stage are 1400°C, 12 MPa, and 2.5 hours.
[0027] In one specific embodiment, a nitrogen protective atmosphere with a purity of ≥99.99% is used during the cryogenic treatment process, which reduces residual stress by 10% to 20% and increases impact toughness by about 10%.
[0028] Compared with the prior art, the technical effects of the present invention are as follows:
[0029] 1. Extreme environmental tolerance: Under conditions of 6 GPa / 1500℃, the hardness remains ≥93 HRA, the compressive strength ≥4500 MPa, and the coefficient of thermal expansion fluctuation ≤5×10 -6 / ℃ (45% lower than traditional materials), can achieve ≥100 synthesis cycles without cracking.
[0030] 2. Improved stability: The diffusion rate of the Co phase is reduced by 60% at high temperature, and the purity (≥99.99%) and integrity (no inclusion defects) of the synthesized large single crystal diamond are significantly improved.
[0031] 3. Process optimization: The density reaches over 99.8%, the grain size deviation is ≤0.3μm, and the batch stability of the material (performance fluctuation ≤3%) is better than the existing technology.
[0032] In summary, this invention effectively solves the failure problem of traditional top hammers, meets the requirements for efficient and stable synthesis of high-purity large single crystal diamond, and has significant industrial application value. Detailed Implementation
[0033] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0034] Example 1
[0035] This embodiment provides a high-pressure resistant cemented carbide top hammer for the synthesis of high-purity large single-crystal diamond, and its specific preparation steps are as follows:
[0036] 1. Raw material preparation
[0037] WC powder: purity 99.95%, average particle size 0.5μm;
[0038] Co powder: purity 99.5%, particle size 0.8-1.0μm, spherical;
[0039] TaC powder: 99% purity, 80nm particle size;
[0040] TiC powder: 99% purity, 20nm particle size;
[0041] Cr3C2 powder: purity 99%, particle size 20μm.
[0042] Mix according to the following weight percentages:
[0043] WC: 85%;
[0044] Co: 6%;
[0045] TaC: 3%;
[0046] TiC: 4%;
[0047] Cr3C2: 2%.
[0048] 2. Raw material mixing and ball milling
[0049] The above raw materials were weighed according to the proportion and placed in a cemented carbide ball milling jar. Anhydrous ethanol was added as the ball milling medium, and the ball-to-material ratio was 7.5:1. The mixture was ball milled for 48 hours under argon protection to obtain a uniform composite powder.
[0050] 3. Drying and sieving
[0051] The ball-milled mixed powder was dried in a vacuum drying oven at 80°C for 5 hours, and then sieved through a 200-mesh sieve under argon protection to remove agglomerated particles.
[0052] 4. Molding
[0053] Cold pressing: The sieved powder is loaded into a high-speed steel mold and pressed into a top hammer blank with a side length of 50mm under a pressure of 50MPa, with a relative density of ≥65%.
[0054] Cold isostatic pressing: After sealing the billet with a rubber sleeve, it is placed in a cold isostatic press and held at 300 MPa for 30 minutes, which increases the relative density to about 78%.
[0055] 5. Gradient sintering
[0056] First stage: Heat to 800℃ at a rate of 5℃ / min, hold for 1 hour to complete degassing and preheating.
[0057] Second stage: Continue to heat to 1400℃ at 8℃ / min, apply 12MPa pressure, hold for 2.5 hours, and carry out liquid phase sintering.
[0058] The third stage: the temperature is reduced to 800°C at a rate of 3°C / min, and then allowed to cool naturally to room temperature to eliminate internal thermal stress.
[0059] 6. Post-processing
[0060] Surface grinding: The surface is ground using a precision grinding machine at a pressure of 0.2MPa and a speed of 150r / min to achieve a surface roughness of ≤0.8μm.
[0061] Cryogenic treatment: The ground top hammer is placed in a liquid nitrogen cryogenic treatment chamber and cooled to -150°C at a rate of 8°C / min. It is then protected with 99.99% pure nitrogen gas and kept at that temperature for 4 hours. Finally, it is heated to room temperature at a rate of 5°C / min to further reduce residual stress and improve toughness.
[0062] Performance test results
[0063] The cemented carbide hammer material prepared in this embodiment has the following performance indicators after testing:
[0064] Hardness: ≥93HRA;
[0065] Compressive strength: ≥4500MPa;
[0066] Density: 99.8%;
[0067] Grain size deviation: ≤0.3μm;
[0068] Fluctuation in thermal expansion coefficient: ≤5×10 -6 / ℃;
[0069] Service life: No cracking after ≥100 cycles of continuous synthesis under 6GPa and 1500℃ conditions;
[0070] The obtained large single-crystal diamond has a purity of ≥99.99% and no obvious inclusion defects.
[0071] Therefore, the cemented carbide hammer material provided in this embodiment exhibits excellent stability, durability and purity under ultra-high pressure and high temperature conditions, and is suitable for the efficient synthesis of high-purity large single crystal diamond.
[0072] Example 2
[0073] The main difference between this embodiment and Embodiment 1 lies in the adjustment of the raw material ratio and sintering process parameters, with the aim of verifying the stability and applicability of the material system under different process windows.
[0074] 1. Raw material preparation
[0075] Choose the following raw materials:
[0076] WC powder: purity 99.9%, particle size 0.6μm;
[0077] Co powder: purity 99.5%, particle size 1.0μm, spherical;
[0078] TaC powder: 99% purity, 70nm particle size;
[0079] TiC powder: 99% purity, 25nm particle size;
[0080] Cr3C2 powder: purity 99%, particle size 25μm.
[0081] Mix according to the following weight percentages:
[0082] WC: 82%;
[0083] Co: 7%;
[0084] TaC: 5%;
[0085] TiC: 5%;
[0086] Cr3C2: 1%.
[0087] Compared with Example 1, the WC content was reduced and the ratio of TaC to TiC was increased to further enhance the high-temperature phase stability and grain boundary pinning effect.
[0088] 2. Raw material mixing and ball milling
[0089] A planetary ball mill was used, and ball milling was carried out for 36 hours under argon protection. The ball-to-material ratio was maintained at 7.5:1, and the medium was anhydrous ethanol.
[0090] 3. Drying and sieving
[0091] After the ball-milled powder was vacuum dried at 90°C for 6 hours, it was sieved through a 200-mesh sieve.
[0092] 4. Molding
[0093] Cold pressing: Pressed at 80MPa, with a relative density of approximately 70%;
[0094] Cold isostatic pressing: holding at 350MPa for 40 minutes increases the relative density to 80%.
[0095] 5. Gradient sintering
[0096] A pressure + vacuum sintering furnace was used, and the process conditions were as follows:
[0097] First stage: Heat to 850℃ and keep warm for 1 hour to complete degassing and preheating;
[0098] Second stage: Heat to 1450℃, apply 15MPa pressure, and hold for 2 hours;
[0099] The third stage: cool down to 750℃ at a rate of 2.5℃ / min, and then let it cool naturally to room temperature.
[0100] Compared to Example 1, the sintering temperature was increased to 1450°C and the cooling rate was slightly slower to further improve grain uniformity and bonding strength.
[0101] 6. Post-processing
[0102] Surface grinding: pressure 0.15MPa, rotation speed 180r / min, surface roughness ≤0.7μm;
[0103] Cryogenic treatment: Cool down to -140℃, keep warm for 5 hours, and then raise to room temperature.
[0104] Performance test results
[0105] The material properties of this embodiment were tested and are as follows:
[0106] Hardness: 92.5 HRA;
[0107] Compressive strength: 4600MPa;
[0108] Density: 99.7%;
[0109] Grain size deviation: ≤0.25μm;
[0110] Fluctuation in coefficient of thermal expansion: ≤4.5×10 -6 / ℃;
[0111] Service life: No cracking after ≥120 cycles of continuous synthesis under 6.5GPa and 1550℃ conditions;
[0112] The obtained diamond has a purity of ≥99.99% and crystal integrity is superior to that of Example 1.
[0113] By increasing the content of TaC and TiC and sintering at higher temperatures and pressures, the top hammer material prepared in this embodiment exhibits better performance in terms of high-temperature phase stability, grain refinement, and cycle life, further verifying the effectiveness of the multi-component nano-reinforcement system and gradient sintering process of this invention.
[0114] Example 3
[0115] The main difference between this embodiment and embodiments 1 and 2 is that the Co content is reduced and the cryogenic treatment conditions are changed to further improve the wear resistance and high-temperature stability of the material.
[0116] 1. Raw material preparation
[0117] The following raw materials are selected:
[0118] WC powder: purity 99.9%, average particle size 0.5μm;
[0119] Co powder: purity 99.5%, particle size 1.0μm;
[0120] TaC powder: 99% purity, 60nm particle size;
[0121] TiC powder: 99% purity, 15nm particle size;
[0122] Cr3C2 powder: purity 99%, particle size 25μm.
[0123] Mix according to the following weight percentages:
[0124] WC: 88%;
[0125] Co: 4%;
[0126] TaC: 3%;
[0127] TiC: 4%;
[0128] Cr3C2: 1%.
[0129] Compared with Examples 1 and 2, the Co content was reduced to decrease metal impurity contamination caused by Co diffusion under high temperature conditions, while maintaining the necessary toughness.
[0130] 2. Raw material mixing and ball milling
[0131] Under argon protection, a planetary ball mill was used for ball milling with a ball-to-material ratio of 7.5:1 and anhydrous ethanol as the medium. The milling time was 60 hours to ensure a highly uniform distribution of each component.
[0132] 3. Drying and sieving
[0133] Dry in a vacuum drying oven at 95℃ for 4 hours, then sieve through a 200-mesh sieve.
[0134] 4. Molding
[0135] Cold pressing: The blank is formed by pressing at 100MPa, with a relative density of about 68%;
[0136] Cold isostatic pressing: After holding at 400MPa for 25 minutes, the relative density increases to 79%.
[0137] 5. Gradient sintering
[0138] First stage: Heat to 800℃ and keep warm for 1 hour to complete degassing and preheating;
[0139] Second stage: Heat to 1380℃, apply 10MPa pressure, and hold for 3 hours;
[0140] The third stage: the temperature is reduced to 850°C at a rate of 3°C / min, and then allowed to cool naturally to room temperature.
[0141] Compared with Example 2, the sintering temperature in this example is lower to avoid excessive grain growth, while the holding time is extended to promote densification.
[0142] 6. Post-processing
[0143] Surface grinding: Grinding is carried out at a pressure of 0.2 MPa and a rotation speed of 120 r / min, and the surface roughness is controlled to be ≤0.9 μm;
[0144] Improved cryogenic treatment: First, the temperature is lowered to -120°C at a rate of 6°C / min and held for 8 hours, then raised to room temperature at a rate of 4°C / min. Compared with Examples 1 and 2, the cryogenic temperature is higher but the holding time is longer, in order to improve toughness and stability.
[0145] Performance test results
[0146] The properties of the cemented carbide hammer material obtained in this embodiment are as follows:
[0147] Hardness: 91.8 HRA;
[0148] Compressive strength: 4400MPa;
[0149] Density: 99.6%;
[0150] Grain size deviation: ≤0.28μm;
[0151] Fluctuation in coefficient of thermal expansion: ≤4.8×10 -6 / ℃;
[0152] Service life: No cracking after ≥95 cycles of continuous synthesis under 6GPa and 1500℃ conditions;
[0153] The obtained large single-crystal diamond has a purity of ≥99.995%, and the content of metal impurities is significantly lower than that in Examples 1 and 2.
[0154] By reducing the Co content, this embodiment effectively reduces Co diffusion under high-temperature conditions, significantly reduces metallic impurity contamination during diamond synthesis, and further improves the purity of diamond. Simultaneously, the improved cryogenic process increases the material's toughness by approximately 12%, ensuring both high purity and extended service life.
[0155] The various embodiments in this specification are described in a progressive manner, with each embodiment focusing on its differences from other embodiments. Similar or identical parts between embodiments can be referred to interchangeably. For the apparatus disclosed in the embodiments, since it corresponds to the method disclosed in the embodiments, the description is relatively simple; relevant parts can be referred to the method section.
[0156] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A hard alloy top hammer for high purity large single crystal diamond synthesis, characterized by, The top hammer is composed of the following components by weight percentage: WC: 80%~88%; Co: 4%~8%; TaC: 2%~5%; TiC: 3%~7%; Cr3C2: 0.5%~2%; Wherein, WC is the hard phase, Co is the binder phase, TaC inhibits grain growth and enhances high temperature stability, TiC is dispersedly distributed in the form of nanoparticles to form pinning effect, and Cr3C2 is used to improve the wettability of Co phase and enhance the oxidation resistance.
2. The top hammer material of claim 1, wherein, The purity of the WC powder is ≥99.9%, and the particle size is 0.4~0.8μm; the Co powder is spherical powder with purity ≥99.5% and particle size 0.8~1.2μm.
3. The top hammer material according to claim 1 or 2, characterized in that, The TaC powder is nanopowder with particle size 50~100nm; the TiC powder is nanopowder with particle size 10~30nm; and the Cr3C2 powder is powder with particle size 10~30μm.
4. A method of producing a high-pressure-resistant cemented carbide top hammer material according to any one of claims 1-3, characterized in that The method comprises the following steps: (1) raw material mixing: mixing WC, Co, TaC, TiC and Cr3C2 by weight percentage, and ball milling for 36~60 hours under argon protection by using a planetary ball mill; (2) drying and sieving: vacuum drying the mixed powder at 80~100℃ for 4~6 hours, and sieving through a 200-mesh screen under argon protection; (3) cold pressing and cold isostatic pressing: cold pressing the powder into a shape under 20~100MPa, and then cold isostatic pressing treatment under 200~400MPa; (4) gradient sintering: in a vacuum sintering furnace, sequentially performing degassing preheating (800℃, 1h), liquid phase sintering (1350~1450℃, 10~20MPa, 2~3h) and slow cooling treatment (3℃ / min to 800℃, natural cooling to room temperature); (5) post-treatment: grinding the sintered top hammer to make the surface roughness ≤0.8μm, and deep cryogenic treatment in liquid nitrogen, temperature reduced to -150℃, holding for 4h, and then increasing the temperature to room temperature.
5. The method of claim 4, wherein, The ball-to-powder ratio during ball milling is 7.5:1, and anhydrous ethanol is used as the ball milling medium.
6. The method according to claim 4 or 5, characterized in that, The pressure holding time of cold isostatic pressing is 20~40 minutes, and the pressure release rate is 50MPa / min.
7. The method of claim 6, wherein, The preferred conditions of the liquid phase sintering stage are 1400℃, 12MPa and 2.5 hours.
8. The method of claim 7, wherein, During the deep cryogenic treatment, a nitrogen gas protection atmosphere with purity ≥99.99% is used, the residual stress is reduced by 10%~20%, and the impact toughness is increased by about 10%.